Search for supersymmetry with jets, missing transverse momentum and at least one hadronically decaying [tau] lepton in proton-proton collisions at √s = 7 TeV with the ATLAS detector - Aad, Georges; Anders, Gabriel (Arxiv, 2012)
A search for production of supersymmetric particles in final states containing jets, missing transverse momentum, and at least one hadronically decaying tau lepton is presented. The data were recorded by the ATLAS experiment in sqrt(s) = 7 TeV proton-proton collisions at the Large Hadron Collider. No excess above the Standard Model background expectation was observed in 2.05 fb-1 of data. The results are interpreted in the context of gauge mediated supersymmetry breaking models with Mmess = 250 TeV, N5 = 3, mu > 0, and Cgrav = 1. The production of supersymmetric particles is excluded at 95% C.L. up to a supersymmetry breaking scale Lambda = 30 Tev, independent of tan(beta), and up to Lambda = 43 TeV for large tan(beta).